Biological and molecular characterization of a new potexvirus isolated from Adenium obesum - Bello, Vinicius Henrique; Nagata, Tatsuya; Marubayashi, Julio Massaharu [UNESP]; Krause-Sakate, Renate [UNESP]; de Sá Andrade Medeiros, Layla; Júnior, José Evando Aguiar Beserra; Rezende, Jorge Alberto Marques; Kitajima, Elliot Watanabe (Springer Nature, 2023)
Adenium obesum plants showing virus-like symptoms were collected in several regions of Brazil. Mottling symptoms like those observed in symptomatic plants in the field were reproduced in mechanically inoculated A. obesum plants. This potexvirus was named “desert rose mottle virus” (DRMoV), and its genome sequence was first determined by high-throughput sequencing and then confirmed by Sanger sequencing. The complete genome of DRMoV is 6,781 nt in length, excluding the poly(A) tail, and five ORFs were predicted in order from 5’ to 3’: Rep-TGB1-TGB2-TGB3-CP. Phylogenetic analysis based on Rep amino acid sequences showed different clustering among potexviruses. These data suggest that RDMoV is a new member of the genus Potexvirus, and the binomial name “Potexvirus adenii” is proposed for its species.